Wind influence on the orientation of estuarine landforms: An example from Lake Illawarra in southeastern Australia. Issue 14 (16th July 2018) - Deng, Junjie; Jones, Brian G.; Rogers, Kerrylee; Woodroffe, Colin D.
Abstract: We propose a type of a quasi‐equilibrium, which describes a convergence of the estuarine system towards a form whose planimetric orientation is along the prevailing winds. By using the microtidal Lake Illawarra in southeastern Australia as an example, we describe sediment convergent and divergent processes that induce such an equilibrium controlled by the complex configuration of the shoreline relative to the prevailing winds. For a complex estuarine sedimentary system with a mixture of non‐cohesive and cohesive sediments, alongshore distribution of fluvial or marine sand deposition and associated subaqueous morphology reflects alongshore redistribution of sediments from rivers and the tidal inlet. The orientation of the second‐order polynomial trend surface of estuarine morphology is consistent with prevailing wind directions. Along the lake shore, there are extensive narrow flats mainly covered by fluvial or marine sands shaped by the prevailing winds. The implementation of the Delft3D flow model coupled with the SWAN wave model driven by idealized prevailing winds indicates the potential of sediment convergent and divergent transport at the embayment and promontory shoreline, which appears to be similar to the alongshore distribution of sandy sediments and the nearshore flats. Alongshore transport of sandy sediments is primarily induced by the wave refraction on the shore, while the currents are more effective in transporting fine‐grained sediments such as mud or clay. Finally, we suggest a conceptual model that describes potential sediment transport of convergence and divergence on the embayment or promontory shoreline that is normal to the prevailing winds. Orientation of the estuary follows the convergence centre of sediment transport driven by the prevailing winds with the largest fetch. A quantitative threshold for such sediment redistribution may be determined in the future. © 2018 John Wiley & Sons, Ltd. Abstract : Estuarine planimetric orientation and sediment distribution are found to be consistent with the prevailing winds. Hydrodynamic modelling shows a striking consistency between estuarine morphology, sediment transport and the prevailing winds. A new conceptual model is thus proposed to describe wind‐controlled sediment redistribution that influences the estuarine orientation.